The courage to be disliked - Kishimi, Ichirō; Koga, Fumitake (United States : IRB states, 2022)
This is a companion version not the original book. Book Preview: #1 The young man was extremely self-conscious, and had been since childhood. He didn't believe in the claims of the philosopher, and saw them as nothing more than fantasy. #2 Greek philosophy has long been a mainstay of philosopher Ichiro Kishimi's life. However, he is well known for his work in Adlerian psychology, which is closely related to Greek philosophy. #3 If everyone is the result of their past incidents, then it follows that everyone's present and future are predetermined. #4 In Adlerian psychology, the past doesn't matter. The present is all that matters
Keywords: Adler; Alfred; 1870-1937 Adlerian psychology Conduct of life Electronic books